Atividade cambial e o efeito de anelamento no xilema secundário em espécies de cerrado - Bosio, Fabio [UNESP] (2015)
This study approached the seasonality in cambial activity and vegetative phenology, the relationship between these events and their relation with wheater and environmental factors, and also the effects of stem girdling in the structure of secondary xylem in Cerrado species. In order to study of seasonality in cambial activity, monthly samples from main stem of Kielmeyera grandiflora (Wawra) Saddi (Calophyllaceae) were collected from September 2011 to December 2012. In the same period, observations of vegetative phenological phases were made to assess the seasonality in leaf production, and to compare these data with cambial activity. In order to certify which environmental and weather features are related with bud opening and onset of cambial activity, it was calculated the mean value of temperature and photoperiod, and obtained the sum of rainfall in a time scale that ranged from 1 to 30 days before bud opening and the onset of cambial activity. After that, the coefficient of variation was calculated to assess the variability between years. In order to evaluate the stem girdling effect in the structure of secondary xylem was conducted an experiment in field with the species Aegiphila verticillataVell (Lamiaceae), composed of two groups, girdling and control. In girdling group, bark and cambium were completely removed from the central portion of main stem, forming a complete ring. The purpose of girdling was to interrupt the polar flow of auxin produced in the crown, and to assess the effect of its disruption in the structure of secondary xylem. In control group, it has not made a girdling in the stem. To distinguish the xylem formed before girdling from xylem formed after the treatment, an incision (03 cm in length) was made in the regions above and below girdling until reaches the vascular cambium. In the same way, in control group an incision in the bark was made at a central point of the ...